ChemInform Abstract: Equatorenes: Synthesis and Properties of Chiral Naphthalene, Phenanthrene, Chrysene, and Pyrene Possessing Bis(1‐adamantyl) Groups at the Peri‐position. Issue 19 (13th May 2014) - Yamamoto, Koji; Oyamada, Naohiro; Xia, Sheng; Kobayashi, Yuta; Yamaguchi, Masahiko; Maeda, Hiroaki; Nishihara, Hiroshi; Uchimaru, Tadafumi; Kwon, Eunsang
Abstract Optical and electrochemical properties of the novel equatorenes are investigated.